Perbandingan Konseptual Jaminan Fidusia Indonesia dengan Security Interest dalam Sistem Common Law: Argumentasi Reformasi Legislasi - Fadhila Salsabila Kusumawardani; Aminah (Jurnal Ragam Pengabdian, 2026)
This research examines the conceptual differences between Indonesian fiduciary security and security interest in the common law system, focusing on ontological foundations, publicity mechanisms, creditor priority structures, and the regulation of dynamic assets. Indonesian fiduciary law is grounded in the transfer of ownership by trust, requiring notarial deeds and administrative registration to establish a proprietary security right with executorial force. In contrast, the common law security interest is based on a contractual security right strengthened by a notice filing system and priority determined by time of registration. The absence of explicit floating charge regulation, limited transparency in priority information, and inconsistencies in insolvency integration reveal structural gaps within the Indonesian framework. Through normative and comparative analysis, this study argues for legislative reform that integrates open notice filing, clearer priority rules, explicit recognition of dynamic and digital assets, and harmonization with cross-border insolvency principles. Such reform aims to enhance legal certainty, transactional efficiency, and equitable protection while maintaining the fundamental characteristics of the national legal system.